Prolife hypocrisy: why inconsistency arguments do not matter - Colgrove, Nicholas (Journal of medical ethics, 2021)
Opponents of abortion are often described as ‘inconsistent’ (hypocrites) in terms of their beliefs, actions and/or priorities. They are alleged to do too little to combat spontaneous abortion, they should be adopting cryopreserved embryos with greater frequency and so on. These types of arguments—which we call ‘inconsistency arguments’—conform to a common pattern. Each specifies what consistent opponents of abortion would do (or believe), asserts that they fail to act (or believe) accordingly and concludes that they are inconsistent. Here, we show that inconsistency arguments fail en masse. In short, inconsistency arguments typically face four problems. First, they usually fail to account for diversity among opponents of abortion. Second, they rely on inferences about consistency based on isolated beliefs shared by some opponents of abortion (and these inferences often do not survive once we consider other beliefs opponents of abortion tend to hold). Third, inconsistency arguments usually ignore the diverse ways in which opponents of abortion might act on their beliefs. Fourth, inconsistency arguments criticise groups of people without threatening their beliefs (eg, that abortion is immoral). Setting these problems aside, even supposing inconsistency arguments are successful, they hardly matter. In fact, in the two best-case scenarios—where inconsistency arguments succeed—they either encourage millions of people to make the world a (much) worse place (from the critic’s perspective) or promote epistemically and morally irresponsible practices. We conclude that a more valuable discussion would be had by focusing on the arguments made by opponents of abortion rather than opponents themselves.There are no data in this work.